Penerapan Metode User-Centered Design dalam Redesign UI/UX Aplikasi Mobile Transjakarta - Luthfia Masruroh Syah; Mia Kamayani (STMIK Banjarbaru, 2025)
The Transjakarta mobile application plays a vital role in supporting public transportation in Jakarta, but many users report poor usability, complicated navigation, and unintuitive interface design. Based on an initial survey involving 20 active users, the application scored only 26.8 on the System Usability Scale (SUS), placing it in the “Poor” category. This study adopts the User-Centered Design (UCD) approach in the redesign process of the application's UI/UX, involving four key stages: understanding the context of use, identifying user needs, designing appropriate solutions, and evaluating the alignment of those solutions with the identified needs. Evaluation was conducted using the SUS method and A/B Testing. The redesign process led to a significant improvement, raising the SUS score 85.25 and showing that 86% of users preferred the new design. Additional features such as “Top-up Balance” and “Transaction History” also received positive feedback. These findings demonstrate that the UCD approach effectively improves usability and user satisfaction, and can serve as a reference for future developments in public service applications.Keywords: A/B Testing; Redesign; System Usability Scale; Transjakarta; User Centered Design AbstrakAplikasi mobile Transjakarta merupakan layanan pendukung transportasi publik di Jakarta yang penting, namun masih menghadapi berbagai masalah dalam kemudahan penggunaan, integrasi fitur, dan tampilan antarmuka yang kurang intuitif. Berdasarkan survei awal terhadap 20 pengguna, skor System Usability Scale (SUS) hanya mencapai 26,8 yang termasuk kategori Poor. Penelitian ini menggunakan pendekatan User-Centered Design (UCD) dalam proses perancangan ulang UI/UX aplikasi, yang melibatkan empat tahapan inti: memahami konteks penggunaan, mengidentifikasi kebutuhan pengguna, merancang solusi desain, serta mengevaluasi kesesuaian solusi terhadap kebutuhan tersebut. Evaluasi dilakukan menggunanan SUS dan A/B Testing. Hasilnya menunjukkan peningkatan signifikan, dengan skor SUS yang naik menjadi 85,25 (kategori Excellent) dan 86% responden lebih menyukai desain baru. Selain itu, fitur baru seperti “Isi Saldo” dan “Riwayat Transaksi” mendapat tanggapan positif dari mayoritas pengguna. Penelitian ini menunjukkan bahwa UCD efektif dalam meningkatkan kualitas pengalaman pengguna serta dapat menjadi acuan dalam pengembangan aplikasi layanan publik berbasis digital.Kata kunci: A/B Testing; Perancangan Ulang; System Usability Scale; Transjakarta; User Centered Design